Desiring the Kingdom : worship, worldview, and cultural formation - Smith, James K. A., 1970- (Grand Rapids, Mich. : Baker Academic, 2009)
Desiring the Kingdom focuses education around the themes of liturgy, formation, and desire. The author contends--as did Augustine--that human beings are "desiring agents"; in other words, we are what we love. Postmodern culture, far from being "secular," is saturated with liturgy, but in places such as malls, stadiums, and universities. While these structures influence us, they do not point us to the best of ends. Smith aims to move beyond a focus on "worldview" to see Christian education as a counter-formation to these secular liturgies. His ultimate purpose is to re-vision Christian education as a formative process that redirects our desire toward God's kingdom and its vision of flourishing. --from publisher descriptioin
Includes bibliographical references and indexes.
Keywords: Liturgics; Christianity and culture; Liturgical adaptation; Christianity -- Philosophy